A room-temperature phosphorescent polymer film containing a molecular web based on one-dimensional chiral stacking of a simple luminophore. Issue 36 (21st April 2017) - Yoshida, Kyohei; Kuwahara, Yutaka; Miyamoto, Koji; Nakashima, Seiya; Jintoku, Hirokuni; Takafuji, Makoto; Ihara, Hirotaka
Abstract : We propose a new approach for a totally organic, room-temperature phosphorescent system with a lifetime on the order of milliseconds. Abstract : We propose a new approach for a totally organic, room-temperature phosphorescent system with a lifetime on the order of milliseconds, which is achieved by promotion of the one-dimensional chiral stacking of a simple, small fluorophore in a solution state. The versatility of this system is highlighted by its good applicability to the fabrication of a phosphorescent polymer film. This paper demonstrates the first example of a room-temperature phosphorescent polymer film prepared with our methodology.